Role of gut microbiome in suppression of cancers - Yao Xu; Zhaoyu Gao; Jiaying Liu; Qianqian Yang; Shunjiang Xu (Gut Microbes)
The pathogenesis of cancer is closely related to the disruption of homeostasis in the human body. The gut microbiome plays crucial roles in maintaining the homeostasis of its host throughout lifespan. In recent years, a large number of studies have shown that dysbiosis of the gut microbiome is involved in the entire process of cancer initiation, development, and prognosis by influencing the host immune system and metabolism. Some specific intestinal bacteria promote the occurrence and development of cancers under certain conditions. Conversely, some other specific intestinal bacteria suppress the oncogenesis and progression of cancers, including inhibiting the occurrence of cancers, delaying the progression of cancers and boosting the therapeutic effect on cancers. The promoting effects of the gut microbiome on cancers have been comprehensively discussed in the previous review. This article will review the latest advances in the roles and mechanisms of gut microbiome in cancer suppression, providing a new perspective for developing strategies of cancer prevention and treatment.